A socialização política dos jovens estudantes do ensino médio no município de Toledo/Paraná - Silva, Francielli Pirolli da (2017)
The theme of this dissertation is the political socialization, in the municipality of Toledo/Paraná. The research object is the young people, aged 16 to 19 years, who are high school students in the public and private schools. The goal is to analyze and identify how they conduct political socialization and what issues, actions, and activities related to politics they participate in. To carry out the proposal of this work, the bibliographic research approached topics such as political culture, political socialization and youth. In the empirical research, 420 questionnaires – quantitative ones, composed of socioeconomic and political questions – were applied to the young people, with the abovementioned ages, distributed among 12 public and 03 private schools. It was found that the means and ways in which young people construct political socialization are established according to the social environment they are inserted and to the socializing agencies they take part in.